Effect of filler loading and chemical modifications on properties of Chitosan/ polypropylene composites - Faisal Amri, Tanjung (Universiti Malaysia Perlis (UniMAP), 2012)
Chitosan filled polypropylene (PP) composites had been prepared using Z-Blade Mixer at temperature 190oC and rotor speed 50 rpm. The effect of chitosan loading and different types of chemical modifications on mechanical properties, morphology and thermal properties of PP/Chitosan composites were studied. The various types of chemical modifications such as acrylic acid (AA), methyl methacrylate (MMA), acetic acid (AAc), 3-aminopropyltriethoxysilane (3-APE) and sodium dodecyl sulfate (SDS) were investigated. The organosolv lignin (OSL) was extracted from coconut shell powder and used as partial treatment with AA and SDS. The results showed that the addition of chitosan into PP matrix reduced the tensile strength, elongation at break, degree of crystallinity (Xc) and activation energy (Ea), whereas the thermal stability and Young’s modulus of composites increased. The chemical modification of chitosan resulted positive effect on mechanical and thermal properties of PP/Chitosan composites. The treated PP/Chitosan composites with AA, MMA, AAc, 3-APE, SDS have higher tensile strength, Young’s modulus, thermal stability, Xc and Ea compared to untreated PP/Chitosan composites. The better interfacial interaction between treated chitosan and PP matrix was proven by the scanning electron microscopy (SEM) study. The FTIR spectra of treated chitosan showed the new functional group from the formation of chemical bonding between chitosan and chemical modifying agent. The treated PP/Chitosan composites with AA and OSL had lower tensile strength and elongation at break, but higher Young’s modulus, thermal stability, Xc and Ea than treated PP/Chitosan composites with AA. The SEM micrographs of treated PP/Chitosan composites with AA and OSL exhibited a rough surface. The effect of OSL to treated PP/Chitosan composites with SDS increased the elongation at break, thermal stability, crystallinity and activation energy, while the tensile strength and Young’s modulus decreased compared to treated PP/Chitosan composites with SDS. The morphology of treated PP/Chitosan composites with SDS and OSL showed the ductile behavior.